Zang Siwei Qingfei Mixture Alleviates Inflammatory Response to Attenuate Acute Lung Injury by the ACE2/NF-κB Signaling Pathway in Mice - Lei, Si; Wu, Shangjie (Combinatorial Chemistry & High Throughput Screening, 2024)
Background Acute lung injury (ALI) is a serious lung disease characterized by acute and severe inflammation. Upregulation of ACE2 and inhibition of the NF-κB signaling pathway attenuate LPS-induced ALI. Objective To explore whether Zang Siwei Qingfei Mixture inhibits the development of ALI through the ACE2/NF-κB signaling pathway. Methods Alveolar type II epithelial cells (AEC II) were identified by immunofluorescence staining and flow cytometry. C57BL/6J mice were treated with LPS to establish an ALI model. Cell viability was assessed using CCK8 assays. The levels of ACE, ACE2, p-p38/p38, p-ERK1/2/ERK1/2, p-JNK/JNK, p-IκBα/IκB-α, p-NF-κBp65 were analyzed by Western blotting. ELISA was applied to detect the levels of TNF-a, IL-6, AGT, and Ang1-7. HE staining was used to observe lung injury. The mRNA expression of ACE, ACE2, and Mas was measured by RT-qPCR. Results AEC II cells were successfully isolated. Treatment with the Zang Siwei Qingfei Mixture resulted in a decrease in ACE, p-p38/p38, p-ERK1/2/ERK1/2, p-JNK/JNK, p-IκBα/IκB-α, p-NF-κBp65 levels, while increasing ACE2 levels. Zang Siwei Qingfei mixture also led to a reduction in TNF-α, IL6, and AGT levels, while increasing Ang1-7 level. Histological analysis showed that Zang Siwei Qingfei Mixture treatment improved the alveolar structure of ALI mice and reduced inflammatory infiltration. The pretreatment with MLN-4760, an ACE2 inhibitor, resulted in opposite effects compared to Zang Siwei Qingfei Mixture treatment. Conclusion Zang Siwei Qingfei mixture attenuates ALI by regulating the ACE2/NF-κB signaling pathway in mice. This study provides a theoretical foundation for the development of improved ALI treatments.
Keywords: ACE2/NF-κB